2010
DOI: 10.1124/jpet.110.171439
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Novel Non-AT1, Non-AT2 Angiotensin Binding Site with Neuronal Cell Death

Abstract: We have discovered a non-AT 1 , non-AT 2 angiotensin binding site in rodent and human brain membranes, which, based on its pharmacological/biochemical properties and tissue distribution, is different from angiotensin receptors and key proteases processing angiotensins. In this study, the novel angiotensin binding site was localized to a specific brain cell type by using radioligand receptor binding assays. Our results indicate that the novel binding site is expressed in mouse primary cortical neuronal membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…As shown in Figure 1, optimal unmasking was observed at PCMB concentrations of 100–300 μM. The optimal PCMB concentration are slightly lower than our initial report [26], but is consistent with subsequent more recent studies [33,56]. Two-way ANOVA of the K D values indicated that the K D for testis was lower at 100 μM than at 300 μM (p<0.01) and that there was a main effect of higher affinity at 100 μM versus 300 μM (p=0.0033).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Figure 1, optimal unmasking was observed at PCMB concentrations of 100–300 μM. The optimal PCMB concentration are slightly lower than our initial report [26], but is consistent with subsequent more recent studies [33,56]. Two-way ANOVA of the K D values indicated that the K D for testis was lower at 100 μM than at 300 μM (p<0.01) and that there was a main effect of higher affinity at 100 μM versus 300 μM (p=0.0033).…”
Section: Resultssupporting
confidence: 91%
“…Among the sulfur-containing organic compounds, only cysteamine and amifostine, inhibited the unmasking by more than 50% in both brain and testis. Glutathione was not included in the primary screening based on a previous observation of its inhibitory effect [56]. Among the non-sulfur containing organic compounds (KCN was included here because it contains a carbon), only mersalyl acid inhibited the unmasking by more than 50% in both brain and testis.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the neuroprotective effects of biphalin, we challenged neuronal cells with glutamate and hypoxia/aglycemia and used two independent approaches (LDH and MTT assays) to determine neuronal injury. LDH is an indicator of plasma membrane integrity and MTT is a widely used indicator of mitochondrial function, and both assays have been proved to be reliable indicators of neuronal injury (Lobner, 2000; Rashid et al, 2010). In our studies biphalin displayed a better ability to maintain integrity of plasma membrane (release of LDH), and mitochondrial function (conversion of MTT) compared to equimolar concentrations of selective OR agonists DPDPE, DAMGO and U 50 488 (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Neurolysin has been shown to be present on the extracellular surface of cortical neurons and is therefore capable of metabolizing Ang I and Ang II in their extracellular environment [65], [66]. Moreover, formation of Ang (1–7) by neurolysin [45] diverts the conversion of Ang I into Ang II, directly counteracting the effects of the latter.…”
Section: Discussionmentioning
confidence: 99%